2011
DOI: 10.1074/jbc.m110.161562
|View full text |Cite
|
Sign up to set email alerts
|

FdC1, a Novel Ferredoxin Protein Capable of Alternative Electron Partitioning, Increases in Conditions of Acceptor Limitation at Photosystem I

Abstract: In higher plants, [2Fe-2S] ferredoxin (Fd) proteins are the unique electron acceptors from photosystem I (PSI).. Whereas FdC1 was capable of electron transfer with FNR, redox potentiometry showed that it had a more positive redox potential than photosynthetic Fds by around 220 mV. These results indicate that FdC1 electron donation to FNR is prevented because it is thermodynamically unfavorable. Based on our data, we speculate that FdC1 has a specific function in conditions of acceptor limitation at PSI, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 58 publications
(57 reference statements)
1
71
0
Order By: Relevance
“…There are several FDX isoforms in Arabidopsis (Hanke et al, 2004). Due to the possible partial redundancy of ferredoxin isoforms, mutants in FDX2 show mild phenotypes (Hanke and Hase, 2008;Voss et al, 2011). This may also explain why in Fe deficiency we see FDX2 protein decrease early (day 2), but we do not see effects on photosynthesis until later (day 4) when also the cytochrome-b 6 f complex and to a lesser extent PSI and the NDHK subunit of the NDH complex become affected.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinsmentioning
confidence: 64%
See 2 more Smart Citations
“…There are several FDX isoforms in Arabidopsis (Hanke et al, 2004). Due to the possible partial redundancy of ferredoxin isoforms, mutants in FDX2 show mild phenotypes (Hanke and Hase, 2008;Voss et al, 2011). This may also explain why in Fe deficiency we see FDX2 protein decrease early (day 2), but we do not see effects on photosynthesis until later (day 4) when also the cytochrome-b 6 f complex and to a lesser extent PSI and the NDHK subunit of the NDH complex become affected.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinsmentioning
confidence: 64%
“…Genetic loss of FDX2 is reported to result in mild phenotypes and affected mainly photoreduction of NADP, while cyclic electron flow via the less abundant FDX1 isoform or alternative Fe-S proteins may help maintain NPQ in FDX2 mutants (Voss et al, 2011;Liu et al, 2013). Chlorophyll fluorescence measurements indicated that both FPSII, which is indicative of linear electron flow, and NPQ, which depends on both linear and cyclic electron flow (Maxwell and Johnson, 2000), are affected by Fe deficiency.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis thaliana plants were all Columbia ecotype and grown under long-day conditions, basically as described previously (Voss et al, 2011). Membrane and soluble protein fractions were prepared from whole plants and isolated chloroplasts and subjected to native-PAGE or SDS-PAGE and immunoblotting as described previously .…”
Section: Methods Plant Materials and Sample Preparationmentioning
confidence: 99%
“…Higher-plant Fds are encoded by a small gene family, with distinct isoforms present in chloroplasts and nonphotosynthetic plastids (Hanke et al, 2004;Voss et al, 2008Voss et al, , 2011. Chloroplasts from C3 plants contain at least two isoforms that accumulate to different levels and share a high degree of sequence identity (Hanke et al, 2004).…”
mentioning
confidence: 99%